Negative optics in vision machines - Parisi, Luciana (AI & society, 2021)
Can machine vision step beyond the ocularcentric metaphysics of the Western gaze and the reproduction of racial capital? Paul Virilio argued that machine vision requires no perceptual response or recognition of the world. The computer’s series of coded impulses mediate the real autonomously from physical and energetic analogies. This article calls “negative optics” this inhuman mode of machine vision that withdraws from the ocularcentric rules of transparency. Not only negative optics offers an internal critique of ocular metaphysics, but it also defies the equation of value between 0 and 1 s that sustains the universal law of capital. The equation of value needs the nullification of the racialized and gendered body to meet the function of surrogate machines feeding the neo-liberal human subject. Here, however, the negative optics of machine vision withdraws matter from the equation insofar as the AI mismatches of concepts and objects requires the formation of socio-technical assemblages amongst surrogates of all kinds. The intricacies of this surrogacy are discussed in connection to artist Elisa Giardina’s video installation entitled, The Cleaning of Emotional Data (2019). This video presents the background to address a surrogate human–machine alliance that steps beyond the human–machine equation of value. By starting from the negativity of the image, the racialized and gendered conditions of techno-social labor under artificial intelligence capitalism show that the equation of value maintains the condition of the zero of blackness, which like matter without form, has no value (On matter beyond the equation of value 2017). Drawing on François Laruelle, the article continues to elaborate the possibilities of a material image without form in terms of what Laruelle calls, the “fractal algorithm of the photo ”. The article concludes that the negative optics of machine vision stands for the alien origination of knowledge, values, materialities that overturn the equation of value through the fractal infinities of 0 s.